ANALYSIS OF SHEARER VERTICAL DIRECTION VIBRATION CHARACTERISTICSUNDER DIFFERENT COAL AND ROCK HARDNESS - MAO Jun; YANG XinWei; CHEN HongYue; SONG QiuShuang (Jixie qiangdu, 2019)
According to shearer vibration problems in the practical work,using multi-body dynamics theory,considering the connection characteristics between walking unit of shearer and scraper conveyor,the support characteristics of adjustment height oil vat,the stiffness of rocker arm of shearer,the connection characteristics between the parts of shearer,vibration angle of shearer,6 degrees of freedom dynamic model in the vertical direction of shearer was established.The vertical direction of shearer drum load was used as an external excitation,and the effect of different coal and rock hardness on vertical direction vibration characteristics of shearer were solved by using numerical analysis method. The results show that the mean of coal cutting impedance has great influence on vibration displacement of front and rear cutting unit when the range is 200 kN/m ～ 400 kN/m,the displacement range of front and rear drum is 13. 42 mm ～ 26. 83 mm、8. 19 mm ～ 16. 37 mm,and the displacement range of front and rear rocker arm is 5. 31 mm ～ 10. 62 mm、3. 32 mm ～ 6. 65 mm.Finally,the results of model is verified by experiment.